Efeitos da associação do beta-caroteno, alfa-tocoferol e do fumo no câncer de pulmão - Saad, Paulo César Bálade (2006)
Cigarettes accounts for the death of millions of people a year worldwide, directly related to lung cancer. Some studies have shown that larger plasmatic indexes of beta-carotene or a great ingestion of foods rich in carotenoids diminish the risk of developing this neoplasia. On the other hand, studies suggest that the smokers' lung can alter the metabolism of beta-carotene, that is, producing greater risk of cell alterations and neoplasias. It is probable that the alpha-tocopherol has beneficial effect on this association. Objective: To evaluate the participation of beta-carotene and alpha-tocopherol in the development of lung cancer induced by urethane and its relationship with cigarette exposition. Material and Method: Balb C mice were divided into 10 groups: G1(cigarette), G2 (cigarette and urethane), G3 (only urethane), G4, G5 and G6 (cigarette, urethane and beta-carotene to 0.25, 0.05 and 0.005%, respectively), G8 (urethane and beta-carotene to 0.25%), G7, G10 and G11 (cigarette, urethane and beta-carotene to 0.25 and alpha-tocopherol 0.25; 0.05 and 0.005%, respectively).The exposition to the cigarette was for 10 minutes, twice a day, 5 days a week, during 16 weeks. For induction of tumors, urethane was administered intraperitonealy, in the dose of 3.0mg/Kg. Nodules and hyperplasias were quantified; morphometric analyses of the nodules were performed. Kruskal-Wallis and of Mann-Whitney tests were used for statistical analysis. Results: Group G3 presented greater number of nodules (P=0.001), smaller stromal fraction (P=0.011) and greater sum of the tumor area (P=0.047) compared to group G2. Group G8 showed smaller number of nodules (P=0.013) and hyperplasias (P=0.05) compared to group G3. Both smaller doses of beta-carotene (G5 and G6) were statistically similar, although with smaller number of nodules when compared to group G4 (P=0.04). Group G4 presented smaller number of hyperplasias than G8, however, the number of nodules did not alter (P=0.045%). Stromal fraction of groups G3 and G4 was similar, although smaller than G2 and G5 (P=0.011). According to the alpha-tocopherol, the stromal fraction of group G7 was greater than the one of the groups G2, G3, G4 and G10 (P=0.011). The 0.25%-beta-carotene diet increased the area of the nodules, demonstrated by the largest area (P=0.03), smaller area (P=0.03), sum of the areas (P=0.018) and average of the areas (P=0.006) in group G4 when compared to G2. Conclusion: According to these results, it was concluded that passive tobacco can be a protecting factor in the evolution of tumors induced by urethane in mice, however, there is no evidence that this could be dose-dependent. The supplementation of beta-carotene in 0.25%-dose can also be a protecting factor, however, associated to passive tobacco it has smaller effect than in lower doses (0.05 and 0.005%). The exposition to cigarette smoke does not alter the number of nodules induced by urethane in mice when in the presence of 0.25%-beta-carotene diet; however the hyperplasia number with the presence of the cigarette diminished. The association of the alpha-tocopherol to the 0.25%- beta-carotene and the passive tobacco produces a protecting factor, mainly in the dose of 0.25%.